Gastronomi Turizmi Bağlamında Turistlerin Yöresel Yiyecek Satın Alma Davranışı: Hatay Örneği - Şimşek, Aykut; Yordam, Selda (TR1010 Dergiler Birligi, 2021)
Tourists want to taste specific local foods which they visit destination. Therefore, it is possible to say that local foods have an important interest in the destination choice of the visitors within the scope of gastronomy tourism, which is gaining importance day by day. Based on this situation, the study aims to determine the factors affecting the purchase of local foods by local tourists visiting the gastronomy city of Hatay. In addition, the study aims to determine whether there is a difference between the demographic characteristics of the tourists in question and the factors that affect their purchase of local foods. In the research, quantitative research methods, the surveytechnique, were used to collect data and the questionnaire was applied to 403 tourists. As a result of the analysis, it was determined that the naturalness of local foods significantly affects the purchasing behavior of tourists. In addition, it has been determined that gender and education level affect the purchasing of local products. However, it was concluded that age, marital status and monthly income are not factors in purchasing local food.